Residual ischemia after revascularization in multivessel coronary artery disease: insights from measurement of absolute myocardial blood flow using magnetic resonance imaging compared with angiographic assessment. - Arnold, JR; Karamitsos, T; van Gaal, W; Testa, L; Francis, J; Bhamra-Ariza, P; Ali, A; Selvanayagam, J; Westaby, S; Sayeed, R; Jerosch-Herold, M; Neubauer, S; et al. (2013)
BACKGROUND: Revascularization strategies for multivessel coronary artery disease include percutaneous coronary intervention and coronary artery bypass grafting. In this study, we compared the completeness of revascularization as assessed by coronary angiography and by quantitative serial perfusion imaging using cardiovascular magnetic resonance. METHODS AND RESULTS: Patients with multivessel coronary disease were recruited into a randomized trial of treatment with either coronary artery bypass grafting or percutaneous coronary intervention. Angiographic disease burden was determined by the Bypass Angioplasty Revascularization Investigation (BARI) myocardial jeopardy index. Cardiovascular magnetic resonance first-pass perfusion imaging was performed before and 5 to 6 months after revascularization. Using model-independent deconvolution, hyperemic myocardial blood flow was evaluated, and ischemic burden was quantified. Sixty-seven patients completed follow-up (33 coronary artery bypass grafting and 34 percutaneous coronary intervention). The myocardial jeopardy index was 80.7±15.2% at baseline and 6.9±11.3% after revascularization (P<0.0001), with revascularization deemed complete in 62.7% of patients. Relative to cardiovascular magnetic resonance, angiographic assessment overestimated disease burden at baseline (80.7±15.2% versus 49.9±29.2% [P<0.0001]), but underestimated it postprocedure (6.9±11.3% versus 28.1±33.4% [P<0.0001]). Fewer patients achieved complete revascularization based on functional criteria than on angiographic assessment (38.8% versus 62.7%; P=0.015). After revascularization, hyperemic myocardial blood flow was significantly higher in segments supplied by arterial bypass grafts than those supplied by venous grafts (2.04±0.82 mL/min per gram versus 1.89±0.81 mL/min per gram, respectively; P=0.04). CONCLUSIONS: Angiographic assessment may overestimate disease burden before revascularization, and underestimate residual ischemia after revascularization. Functional data demonstrate that a significant burden of ischemia remains even after angiographically defined successful revascularization.